2007
DOI: 10.1021/tx600347k
|View full text |Cite
|
Sign up to set email alerts
|

Uranyl Acetate as a Direct Inhibitor of DNA-Binding Proteins

Abstract: Zinc finger proteins, one of the largest families of DNA-binding proteins in higher eukaryotes, are so named because they require zinc ions for appropriate structure and function. Dysregulation of zinc finger-containing DNA transcription and repair proteins has been proposed as a potential mechanism for the toxic effects of some metal ions. Uranium metal has been reported to be both a cytotoxic and a genotoxic agent. We hypothesized that these toxic effects of uranium might be due to its ability to directly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…Xeroderma Pigmentosum, Complementation Group A (XPA) has a single C4 zinc finger that is sensitive to other carcinogenic metals such as arsenic (Piatek et al, 2008; Zhou et al, 2011; Hudson et al, 2015) and zinc content of XPA was reduced after treatment with UA. UA was previously reported to interfere with the DNA binding capacity of the C 2 H 2 zinc finger protein specificity protein 1 (Sp1) (Hartsock et al, 2007) and UA treatment caused zinc loss from this protein as well as another C2H2 zinc finger protein, aprataxin (APTX). The IC 50 values for zinc loss were between 1 and 3 μM for each of these zinc finger proteins suggesting that UA may interfere with DNA repair at much lower concentrations than required to cause DNA damage and cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xeroderma Pigmentosum, Complementation Group A (XPA) has a single C4 zinc finger that is sensitive to other carcinogenic metals such as arsenic (Piatek et al, 2008; Zhou et al, 2011; Hudson et al, 2015) and zinc content of XPA was reduced after treatment with UA. UA was previously reported to interfere with the DNA binding capacity of the C 2 H 2 zinc finger protein specificity protein 1 (Sp1) (Hartsock et al, 2007) and UA treatment caused zinc loss from this protein as well as another C2H2 zinc finger protein, aprataxin (APTX). The IC 50 values for zinc loss were between 1 and 3 μM for each of these zinc finger proteins suggesting that UA may interfere with DNA repair at much lower concentrations than required to cause DNA damage and cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…There is limited evidence that uranium may interact with zinc finger proteins. One study demonstrated that at concentrations equal to or greater than 10 μM, uranyl acetate (UA) disrupted the DNA binding activity of two purified zinc finger proteins, Aart and specificity protein (Sp)1 in vitro (Hartsock et al, 2007). Furthermore, poly(ADP-ribose) polymerase-1 (PARP-1) was identified as a uranium binding protein using affinity chromatography and mass spectrometry approaches (Dedieu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…AP1 and NF-κB, through a nonspecific protein domain interaction manner. 57 Cadmium (Cd 2+ ) has been reported to inhibit the activity of mismatch repair (MMR) complex Msh2-Msh6 via binding at multiple nonspecific binding sites of this MMR complex. 58 This directly and indirectly damaged DNA must be repaired correctly to allow it to duplicate accurately.…”
Section: Dna Damage Responses To Genotoxicantsmentioning
confidence: 99%
“…Previous studies have suggested that the type II secretion system has an essential role in localizing several metal-containing proteins on the outer surface of the cell Mehta et al, 2006). Uranium has a high affinity for DNA, which can result in DNA strand breakage and inhibition of DNA-protein interactions (Hartsock et al, 2007;Matsuda & Nakajima, 2012;Yazzie et al, 2003;Zobel & Beer, 1961). Thus, exposure to U(VI) could be expected to result in DNA damage.…”
Section: Protein and Dna Damagementioning
confidence: 99%